Anti-biofilm multifunctional coating for medical devices - Ajdnik, Urban (visokošolska dela, 2021)
The aim of this Doctoral Dissertation was to develop an anti-biofilm multifunctional coating of the next generation for medical devices, and to gain understanding of the solid/liquid interactions between the components of the polyelectrolyte-surfactant complex (chitosan, lysine-based surfactant) as a colloidal formulation (coating) and solid surface of PDMS, with subsequent study of the detailed surface characteristics of this kind of functionalised materials and further examination of the bioactive properties of the coatings: i) Protein interactions, ii) Microbiology testing and iii) Biocompatibility assays. The interactions between positively charged biopolymer chitosan and an anionic surfactant derived from lysine (77KS) were studied with turbidity and surface tension measurements, %-potential and Dynamic Light Scattering. Chitosan and 77KS form complexes which reverse their charge at higher 77KS concentration, forming larger aggregates that were loaded with drugs (amoxicillin, AMOX). A QCM-D study showed irreversible adsorption of the coatings on a model silicone (polydimethylsiloxane; PDMS) surface, even after the rinsing step, while their presence and homogeneity were confirmed via surface analyses using XPS and ToF-SIMS. The effect was also examined of the ionic strength and of the ultraviolet/ozone (UVO) activation of the PDMS films on the adsorption behaviour of the formulations. An important part of this study was devoted to understanding the underlying adsorption phenomena and identifying the mechanisms associated with biofouling. The adsorption of a number of proteins was investigated, together with their mixture on PDMS surfaces. Different proteins with different physicochemical properties were tested (bovine serum albumin, fibrinogen, gamma globulin and their mixture). Adsorption experiments were performed with a quartz crystal microbalance. The adsorption properties of the test proteins were investigated. Moreover, adsorption of proteins was also followed through %-potential measurements, with comparison of the results of both techniques. IX The additional layer of anionic and hydrophilic hyaluronic acid as an inner layer improved protein-repelling behaviour, due to the formation of a highly hydrated layer in combination with steric hindrance. The last part of the Doctoral Dissertation deals with the preliminary assessment of real applications. For this purpose, real samples were used, i.e. materials, which are among the most commonly used as medical devices, namely, PDMS and medical stainless steel AISI 316LVM in the form of discs. The biocompatibility using mouse fibroblasts L929 and antimicrobial activity against Escherichia coli and Staphylococcus aureus were studied using PDMS and AISI 316LVM medical grade stainless steel as real materials with applied coatings, to show the applicability of the developed coatings on real, not only model surfaces. Bioactive coatings on biomaterial surfaces were confirmed by ATR-FTIR and with a change in the water contact angle. Although coatings provide antibiofilm properties in all cases, coating PDMS/Chi-77KS/HA lowered the presence of bacteria by 85% in the case of Escherichia coli, while PDMS/Chi-77KS/AMOX improved the antibiofilm behaviour by 81%. To conclude, all coatings are biocompatible, based on the criteria of ISO 10993-5 under the applied conditions.
Keywords: biofilm; biofilmi; chitosan; disertacije; hitozan; implantacijski medicinski pripomočki; medical devices; medicinski pripomočki; polisaharidi; polysaccharides; površinsko aktivne snovi; prevleke; silicone; silikon; surfactant